RESEARCHING FAMILY STORIES USING THE GENOGRAM: FORMING A NEW QUALITY OF FAMILY RELATIONSHIPS THROUGH NARRATIVE RECONSTRUCTION OF CONTEXT - Лапіна, Маріанна (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article examines the problem of improving the quality of family relationships through the narrative reconstruction of the context of family histories. Under current wartime conditions, Ukrainian families are experiencing significant transformations, acute crises, and forced changes that profoundly affect their cohesion and psychological resilience. In such circumstances, the importance of restoring emotional connections, developing new models of mutual understanding, and reinterpreting family experience as a crucial condition for maintaining and rebuilding individual psychological resources becomes especially pronounced. The study of intergenerational ties and the reinterpretation of family narratives offer opportunities for a deeper understanding of the dynamics of family relationships. This, in turn, facilitates more effective coping with the complex social processes that Ukrainian society is undergoing today and provides the foundation for developing adaptive and supportive models of interaction within families. Research aim. The aim of the study is to analyze how shifting the context of clients’ family histories contributes to the emergence of new meanings, which subsequently leads to the restoration or improvement of family relationships. Methods. The research employed a qualitative approach based on the analysis of psychotherapeutic cases. The primary tool was the genogram, which enabled the structuring of information about intergenerational connections and events, as well as the identification of recurring patterns. Additionally, a narrative approach was used to explore meaning-making processes and their transformation in the course of therapy. The analysis was conducted within the framework of M. Bowen’s family systems theory and the constructivist ideas of L. Hoffman and W. Ludwig. Conclusions. The findings indicate that reinterpreting and assigning new meanings to family histories within systemic family therapy serves as a key mechanism of therapeutic change. This process contributes to the improvement or restoration of family relationships, enhances the level of differentiation, and fosters the development of more flexible and adaptive models of family interaction.